Sustainability of Lesson Study on The Lesson Study for Learning Community (LSLC) Program in Batu City East Java Province - Budiyanto, Moch. Agus Krisno; Rahardjanto, Abdulkadir; Hadi, Samsun; Husamah, H. (Journal of Education Reseach and Evaluation, 2021)
LSLC was an innovative learning program. Much research has been done regarding the implementation of LSLC, but few have focused on its sustainability. This study aimed to discover the sustainability of LSLC in Batu City. This study was a quasi-research using multivariate multidimensional scaling analysis. The population used was all the piloting LS schools and LSLC experts from universities. The results obtained present a good result on the development side of students’ cognitive, affective, and psychomotor domains. Good development was revealed in the dimensions of pedagogic, competence, and commitment. In the subsidy and socio-cultural dimensions, shows unfavorable results and requires serious attention. It can be concluded that the sustainability of LSLC requires special attention to several dimensions. Therefore, various studies that can be focused on that dimension need to be done, so that the right model/solution can be found to ensure the sustainability.